Understanding alcohol use and changes in drinking habits among people with a severe mental illness: a qualitative framework analysis study - Puddephatt, Jo-Anne; Makin, Harriet; Gage, Suzanne H.; Jones, Andrew; Goodwin, Laura (Frontiers in Psychology, 2023)
Introduction: Individuals with a severe mental illness (SMI) are more likely to drink at harmful levels or abstain. While it is known that drinking patterns change over time, the reasons for this among those with a SMI are unclear. This study aimed to i) explore the experiences with alcohol, particularly in relation to mental health symptoms, and ii) how drinking patterns have changed over time, among individuals who have a SMI diagnosis, who either currently drink alcohol or no longer drink. Methods: One-to-one semi-structured telephone interviews were conducted to address the study aims. Current drinkers' alcohol use was assessed using the Alcohol Use Disorder Identification Test. A framework analysis was used to address the study aims with a specific focus on the differences in the experiences with alcohol use between current and former drinkers. Results: 16 participants were interviewed, and five themes were developed. The analysis highlighted how alcohol was increasingly used to cope with i) trauma, ii) SMI-related symptoms, or iii) stress. Among those with a SMI, non-drinking was facilitated through declines in SMI-related symptoms, previous negative consequences due to alcohol and changing the social environment. Current drinking habits were facilitated through changes in the reasons for drinking and adopting different alcohol moderation techniques. Discussion: Among those with a SMI diagnosis and who either currently drink alcohol or no longer drink, our findings support the self-medication hypothesis and drinking motives model. However, our findings indicate the need for further development of drinking to cope with a focus on symptoms of a SMI and trauma. Our findings also have implications on specialist alcohol and mental health services, the need to improve individuals' understanding of SMI, and the need to identify reasons for drinking among those with a recent diagnosis of a SMI.